Highlights of the 2017 European AIDS Clinical Society (EACS) Guidelines for the treatment of adult HIV‐positive persons version 9.0. Issue 5 (1st March 2018) - Ryom, L; Boesecke, C; Bracchi, M; Ambrosioni, J; Pozniak, A; Arribas, J; Behrens, G; Mallon, PGM; Puoti, M; Rauch, A; Miro, JM; Kirk, O; et al.
Abstract : Background: The European AIDS Clinical Society (EACS) Guidelines have since 2005 provided multidisciplinary recommendations for the care of HIV‐positive persons in geographically diverse areas. Guideline highlights: Major revisions have been made in all sections of the 2017 Guidelines: antiretroviral treatment (ART), comorbidities, coinfections and opportunistic diseases. Newly added are also a summary of the main changes made, and direct video links to the EACS online course on HIV Management. Recommendations on the clinical situations in which tenofovir alafenamide may be considered over tenofovir disoproxil fumarate are provided, and recommendations on which antiretrovirals can be used safely during pregnancy have been revised. Renal and bone toxicity and hepatitis C virus (HCV) treatment have been added as potential reasons for ART switches in fully virologically suppressed individuals, and dolutegravir/rilpivirine has been included as a treatment option. In contrast, dolutegravir monotherapy is not recommended. New recommendations on non‐alcoholic fatty liver disease, chronic lung disease, solid organ transplantation, and prescribing in elderly are included, and human papilloma virus (HPV) vaccination recommendations have been expanded. All drug–drug interaction tables have been updated and new tables are included. Treatment options for direct‐acting antivirals (DAAs) have been updated and include the latest combinations of sofosbuvir/velpatasvir/voxilaprevir and glecaprevir/pibrentasvir. Recommendations on management of DAA failure and acute HCV infection have been expanded. For treatment of tuberculosis (TB), it is underlined that intermittent treatment is contraindicated, and for resistant TB new data suggest that using a three‐drug combination may be as effective as a five‐drug regimen, and may reduce treatment duration from 18‐24 to 6‐10 months. Conclusions: Version 9.0 of the EACS Guidelines provides a holistic approach to HIV care and is translated into the six most commonly spoken languages.